Tari Nulang Mas dalam Kehidupan Sosial Budaya Masyarakat Dusun Sirih Sekapur Kecamatan Jujuhan Provinsi Jambi - AG, Noerin Celty; Surherni, Surherni (Lembaga Yasin AlSys, 2025)
This study is motivated by the importance of preserving traditional arts as an integral part of the sociocultural life of local communities. The purpose of this research is to analyze the Tari Nulang Mas within the context of the social and cultural life of the Dusun Sirih Sekapur community, Jujuhan District, Jambi Province. A descriptive-analytical method was employed, with data collected through observation, interviews, and documentation. The data were qualitatively analyzed using Koentjaraningrat’s cultural anthropology theory and Y. Sumandiyo Hadi’s functional theory. The findings reveal that Tari Nulang Mas serves not only as a form of entertainment but also as a medium for conveying cultural values, strengthening collective identity, and symbolically representing the Dusun Sirih Sekapur community. The dance also fulfills a social function in the preservation of local culture, as evidenced by its role in traditional cultural conservation events. The study concludes that Tari Nulang Mas plays a vital role in maintaining the continuity of local culture, reflects the close relationship between art, custom, and social life, and demonstrates that traditional dance is a crucial element within the cultural system of the community.